Research on Switching Characteristics of 3 300 V Full SiC MOSFET Power Module - Kangkang SUN; Yanping CHEN; Lanyuan XIN; Xiaonian WANG; Kaiqing YU; Changfeng HU (机车电传动)
Depending on the advantages of SiC MOSFET with faster switching and lower on-state losses, the switching characteristics of a 3 300 V full SiC MOSFET device were studied to make better use of the device. Firstly, the switching processes of the SiC device were illustrated in theory, and the quantifiable method was provided; secondly, the effects of gate drive resistors, junction temperature and stray inductance on switching characteristics were investigated; finally, a prototype test was carried out. The results indicated that the switching characteristics optimizing method as discussed can provide application guidance to the full SiC invertors.